Adequate Funding Panacea to Science Education Problems in Nigerian Schools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Funding is critical for the successful implementation of science education programs in educational institutions. Adequate funding is essential for realizing the objectives of science education in schools. This paper examines the importance of adequately funding science education in Nigerian schools. Secondary data were utilized, collected from government documents, print resources, and online publications. Content analysis was used to narrow the literature to the theme of the study. The findings indicate that adequate funding of science education in Nigeria will lead to the provision of infrastructure facilities, laboratories, ICT centers, libraries, science instructional resources, and employment of competent science teachers, effective capacity building, and the successful implementation of STEM education programs. The paper also highlights that proper funding can enhance the quality of education by enabling continuous teacher training, fostering innovative teaching methodologies, and improving overall student outcomes. Based on these findings, the paper recommends that the government should increase the budgetary allocation for education, with a specific focus on prioritizing science education to ensure sustainable development and global competitiveness.